Evaluasi Pengelolaan Dana Operasional Kecamatan Binamu Kabupaten Jeneponto - Amin, Aqeel Fadhlurrahman; Ardieansyah, Ardieansyah; Nalien, Elvira Mulya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the effectiveness of operational fund management in Binamu District, Jeneponto Regency. The focus of this study is to analyze the planning, organizing, implementing, and supervising process of sub-district operational funds and to identify factors that influence their management. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study indicate that the management of operational funds in Binamu District has not been fully optimal. There are several obstacles in the fund management process, including limited human resources who are competent in financial management, lack of transparency in reporting, and minimal supervision of the use of funds. This study recommends increasing the capacity of sub-district officials in financial management, strengthening the internal supervision system, and increasing transparency and accountability in financial management, lack of transparency in reporting, and minimal supervision of the use of funds. This study recommends increasing the capacity of sub-district officials in financial management, strengthening the internal supervision system, and increasing transparency and accountability in the management of sub-district operational funds.